Marx ve Fromm’un yabancılaşma ve sevgi kavramları bağlamında insan-robot ilişkisi - Köse, Leyla (My University, 2019)
The aim of this study is examined the relationships of those who prefer to have emotional relationships with robots which have weak artificial intelligence in the context of Marx and Fromm's concepts of alienation and love. At first Marx and Fromm’s alienation and love concepts were explained. After that the information was collected from newspapers and interviews that explain information about Lily, James and Davecat’s relations. In the light of this information, whether the human-robot relationship is a love relationship according to Marx and Fromm is tackled. Then it was discussed whether this relationship was alienation according to Marx and Fromm.

Bu çalışmanın amacı zayıf yapay zekaya sahip robotlarla duygusal ilişki yaşamayı tercih eden kişilerin bu ilişkilerini Marx ve Fromm’un yabancılaşma ve sevgi kavramları bağlamında incelemektir. Öncelikle Marx ve Fromm’un yabancılaşma ve sevgi kavramları açıklanmıştır. Sonra robotla ilişki yaşayan Lily, James ve Davecat’in ilişkileri ile ilgili gazete haberlerinden ve röportajlardan bilgi toplanmıştır. Bu bilgiler ışığında insan-robot ilişkisinin Marx ve Fromm’a göre bir sevgi ilişkisi olup olmadığı ele alınmıştır. Ardından bu ilişkinin Marx ve Fromm’a göre yabancılaşma olup olmadığı tartışılmıştır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Karl Marx; Erich Fromm; Alienation; Love; Robot; Yabancılaşma; Sevgi